Science teachers innovation in overcoming learning challenges during Pandemic Covid-19: A Reflection - Mohammad Hafiz Sulung; Erman Erman (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
This study aimed to find out the challenges of online learning experienced by schools during the pandemic and explore information from the innovations it has carried out in science learning for students at Muhammadiyah junior high school 7 Cerme, Indonesia. Data collection in this study was carried out using interviews, observations, and documentation to identify challenges and innovations in online learning. The data obtained are challenges and innovations during online learning. These challenges include lack of teacher resources, difficulty monitoring teachers in the implementation of learning, difficulties in monitoring students in learning activities, low IT skills, more time in preparing for learning, lack of student motivation to learn, not having devices, and constrained by internet networks, and students lazy to study. The innovations are improving science and technology in learning and monitoring teacher learning through online journals and learning applications. Next, independent home visits of students, conducting training on the use of IT, using online learning media that are mastered by teachers and understood by students, preparing learning materials properly, and independently providing materials and assignments to students. The results of the reflection show that the implementation of online learning is still carried out even though it has limitations that lead to the emergence of several challenges from both teachers and students. Involvement between teachers and students needs to be maximized by improving teacher skills and student learning habits, which are the demands of the current technological era. So limited face-to-face learning is carried out, which combines face-to-face learning in class with online learning to reduce current challenges.